Taxpayer responsiveness to taxation: Evidence from bunching at kink points of the South African income tax schedule - Neryvia Pillay Bell (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The author applies the bunching methodology to South African administrative tax data over the period from 2011 to 2017 to investigate the responsiveness of individual taxpayers to changes in marginal personal income tax rates. She finds significant evidence of bunching among the self-employed but no evidence of bunching among wage earners. Among the self-employed, bunching is greatest at the highest kink in the income tax schedule and smallest at the lowest kink. Female self-employed exhibit greater bunching behaviour than male self-employed, and responsiveness appears to decrease with age. The responsiveness of the self-employed appears to be due to tax avoidance by shifting income into future periods through retirement fund deductions, as well as a real labour supply response. Despite the significant excess bunching observed, the implied elasticities of taxable income-under the assumption of a uniform heterogeneity distribution around the kink-are not very large.
Keywords: H24; H31; O12; 330; bunching; elasticity of taxable income; personal income taxation; South Africa